Android-Based E-commerce Design for Ceramic Sales at Material Stores Using the Up-Selling Method - Lili Saputri; Aninda Muliani Harahap (LPPM Universitas Islam 45 Bekasi, 2024)
In today's rapidly growing digital era, information systems are one of the important aspects of managing a business. Especially in the trading industry, such as ceramic sales, the use of information technology can provide a significant competitive advantage. UD Sinar Debora is a shop engaged in the sale of materials. In terms of sales, UD Sinar Debora Sibolga has also experienced a significant increase, especially in the ceramic sales section. The problem faced at the ceramic material shop is that the promotions carried out have not been effective, only done conventionally, buying and selling transactions are still done manually. Therefore, it is necessary to have a web-based digital marketing application as a strategy to expand marketing and facilitate sales reach. To overcome the above problems, it is necessary to have a product marketing strategy, one of which is Up Selling. This method is used to increase sales achievement by introducing new products or other best products. By using the upselling method, UD Sinar Debora material store can implement a digital marketing strategy with clear direction and evaluation.